(3RHOI GdWHs - (3CHh EHQGgje , ESeGYjd Hf GdMSf GdMSjfj GdLQLGfj,J (B531 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg hGdUdGI hGdSdGe Ydi SjOfG Yde Cf aVd GdWH heOGhGJg s
(3BNQgG (B:s
(3hGf cGf dge jQLY (B((3RGO efg(B) (3hEf de jcf dge jQLY GMOK efg s
(3fSNI KGfjIs
(3ZjQ ebQhA GdBNQs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B308s
Keywords: (3GdWHs